Acceptability and nutritional value of sorghum–mung bean cookies with variations in sweeteners and fats - Taufiq Firdaus Al Ghifari Atmadja; Nur Arifah Qurota A'yunin; Luthfi Yulmiftiyanto Nurhamzah; Almira Nuraelah; Aulia Putri Wahyuningtyas (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2026)
The main ingredient in cookies is typically wheat flour, which contains gluten and has a high glycemic index. This makes it unsuitable for individuals with gluten intolerance or those requiring low-glycemic index snacks. This study aimed to develop gluten-free cookies using a sorghum–mung bean flour combination while comparing two sweeteners (palm sugar and stevia) and two types of vegetable fats (margarine and virgin coconut oil (VCO)) in terms of sensory quality and nutritional content. The study employed an experimental design using a Randomized Complete Block Design (RCBD) with five treatment formulations and two replicates, totaling ten samples, conducted from May to August 2025. Organoleptic tests were performed at the Food Culinary Laboratory, Faculty of Health Sciences, Universitas Siliwangi, while proximate analyses were conducted at the Food and Nutrition Laboratory, Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia. The formulations included F0 (wheat–sorghum flour, granulated sugar, margarine), F1 (sorghum–mung bean flour, palm sugar, margarine), F2 (sorghum–mung bean flour, palm sugar, virgin coconut oil (VCO)), F3 (sorghum–mung bean flour, stevia, margarine), and F4 (sorghum–mung bean flour, stevia, VCO). Data were analyzed using the Kruskal–Wallis and One-Way ANOVA tests. The results indicated significant differences in all hedonic parameters (color, texture, aroma, and taste) and nutrient content among the formulations (p < 0.001). Formulation F3, which consisted of sorghum–mung bean flour, stevia, and margarine, demonstrated the highest acceptability. In conclusion, cookies made from sorghum and mung bean flours with natural sweeteners and vegetable fats have the potential to be gluten-free, low-glycemic snacks suitable for functional food development.